The Impact of Globalization on the Development of Political Communication in Indonesia - Musliamin Musliamin (State Islamic Institute of Bone, Indonesia, 2022)
The purpose of this study the impact of globalization on the development of political communication in Indonesia as one of the countries affected by the use of social media. This study uses a literature review design, which is a research method used to systematically and explicitly synthesize a concept from previous research articles. The source of data in this research is by searching articles in several databases such as Garuda, EBSCO, IISTE , Social Sciences and Google Scholar. The results of the research show that Indonesia, which is currently a political issue, has become a political movement and communication has become a tool capable of channeling political messages (demands and support) to power for processing. Through the influence of digital media, the space for communication and political participation is increasingly open by increasing the possibility of interaction between important elements in it, namely parties and state institutions which are referred to as elites and citizens or non-elite, which means that currently the government is faced with a society that can gather strength together by fight for their interests. Through the formation of social networks that allow them to coordinate, open space for political debate , build interactive public spaces, mobilize and coordinate collective action. In addition, through the development of internet media, two-way communication has opened up which allows the delivery of aspirations to the government directly.